What Makes Children Work? The Participative Trajectory in Domestic and Pastoral Chores of Children in Southern Mongolia. (September 2016) - Michelet, Aude
Abstract: This article presents an ethnographic study of how children in rural southern Mongolia became competent at pastoral and domestic chores in the years 2006 and 2008–2009. Previous research shows that children's spontaneous interest in learning to work in order to be helpful is cross‐culturally pervasive. Little attention has, however, been paid to the fluctuating nature of children's motivation. In this article, I argue that like learning, motivation needs to be "situated." Following six children's trajectory of participation in work activities at different ages, we see that their involvement was paved by different injunctions from adults, who at times welcomed or required their participation, and at others challenged or rebuffed their involvement. I examine how these children responded to these different modalities of participation and how those shaped their learning practices and motivation to work. The study demonstrates the importance of disentangling children's motivation to learn and participate from children's motivation to work.